Exploring the Correlation Between Effective Internal Communication and Employee Performance in Higher Education Institutions in Ghana: A Study of the University of Health and Allied Sciences, Ho - Akwensivie, Emeli McJames (UniMAC-GIJ, 2021)
In any organization where information is conveyed from one person to another through both verbal and nonverbal means, communication is unavoidable. The University of Health and Allied Sciences (UHAS), like any other organization, uses communication in their everyday activities, both formally and informally, in exchanges between superiors and subordinates, as well as among coworkers. This study argues that there is strong negative correlation between effective communication systems and the performance of the personnel at UHAS and that there is a link between good corporate communication and good employee performance. This study deployed mixed methods, both quantitative (survey questionnaire) and qualitative (in-depth interviews) as well as peer review articles from journals and JOSTER, and using simple random, purposive and convenient sampling techniques to select 200 respondents, it explores the routes of communication which deemed the most useful by employees as well as impediments and failures in UHAS's communication mechanisms. The analysis was done using mean, median, standard deviation, and correlation results. Findings revealed that the most common communication systems are face-to-face, telephone, written memos, email/internet, and grapevines, with written memos being the most useful route of communication. Employees at UHAS also perform admirably. Selective listening, distraction, time pressure, communication overload, and information distortion have all been identified as communication system hurdles and failures. It concludes that various indicators of employee performance are found to be related to various measures of effective organizational communication. It therefore recommends that management should take all necessary steps to rove all the barriers of communication and make use of internet sources of sharing information.
Thesis
Keywords: Internal Communication, Employee Performance, Higher Education Institutions, Ghana, University of Health and Allied Sciences, Ho